Preparation method and application of ZJM-8 molecular sieve containing phosphorus and aluminum components
Through a new preparation method, ZJM-8 molecular sieve with a new topological structure was obtained, which solved the problem of limited types of existing molecular sieve structures, achieved higher pore utilization and specific surface area, and expanded its catalysis and adsorption application potential in the field.
Patent Information
- Application Number
- CN202310000216.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-02
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-01-02
AI Technical Summary
In the prior art, the topological structure of molecular sieves is limited, and it is difficult to meet the needs of new catalytic and adsorption applications.
A new preparation method is adopted to form a gel by mixing the template agent and water and adding an aluminum source, phosphorus source and silicon source, and obtaining a ZJM-8 molecular sieve through hydrothermal reaction, followed by high-temperature calcination to obtain a novel topology Structural phosphorus-containing aluminum component ZJM-8 molecular sieve.
The prepared ZJM-8 molecular sieve has a new topological structure, which improves the variety of molecular sieve. Due to its high pore utilization rate and large specific surface area, it has a wide range of adsorbent application prospects.
Smart Images

Figure CN116199240B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of molecular sieves, and in particular to a preparation method and application of a ZJM-8 molecular sieve containing phosphorus and aluminum components. Background Art
[0002] Aluminophosphate molecular sieve is a type of porous material with aluminum phosphate as the skeleton structural unit. In 1982, the UOP company in the United States reported the synthesis of aluminum phosphate molecular sieve for the first time, breaking the situation that traditional molecular sieves are composed of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron as the skeleton structural units, and at the same time greatly enriching and expanding the structural types and application range of molecular sieves. Due to the properties of aluminum phosphate molecular sieves, the Al-OP bonds contained in them are more flexible and changeable than the bond angles of Si-O-Al bonds in silicon-aluminum molecular sieves, which makes aluminum phosphate molecular sieves have more structural possibilities. In recent years, more and more aluminum phosphate molecular sieves with new structures have been synthesized and reported, and are widely used in catalysis, adsorption separation and other fields.
[0003] The ABC-6 family has about thirty series of zeolites or aluminum phosphate frameworks, which is the largest group of related structures among the known zeolite structure types so far. The topological structures of these structures are all stacked with parallel six-membered rings along the c-axis direction of the hexagonal unit cell. The vertex of each six-membered ring is a TO4 tetrahedron (T = Si, Al, or P, etc.). The six-membered ring can occupy one of three positions in the unit cell, usually called A, B and C. The stacking of the six-membered rings produces various polyhedral cages in the molecular dimension. These characteristic cages can accommodate various types of ions, water molecules and gas molecules, and therefore play an important role in the fields of adsorption, diffusion and catalysis. At the same time, due to the confinement effect of their characteristic cages, these molecular sieves are currently one of the best industrial catalysts for methanol to olefins (MTO) reactions.
[0004] Considering that the existing topological structures of molecular sieves that can be artificially synthesized are still very limited, in order to enrich the types of molecular sieves and explore the synthesis technology of new molecular sieve framework structures, this application proposes a method for synthesizing a new molecular sieve containing phosphorus and aluminum components. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a preparation method and application of ZJM-8 molecular sieve containing phosphorus and aluminum components.
[0006] To solve the technical problem, the solution of the present invention is:
[0007] The present invention provides a method for preparing a ZJM-8 molecular sieve containing phosphorus and aluminum components, comprising:
[0008] (1) preparing a template solution by combining a template and water, and sequentially adding an aluminum source, a phosphorus source and a silicon source under stirring, and uniformly mixing to form a gel; wherein the molar ratio of the aluminum source calculated as Al2O3: the phosphorus source calculated as P2O5: the silicon source calculated as SiO2: the template: the water is 1: (0.7-1.3): (0-0.6): (0.5-1.5): (20-100);
[0009] (2) transferring the gel to a hydrothermal reactor for a hydrothermal crystallization reaction; the reaction temperature is 180 to 250° C. and the reaction time is 1 to 7 days;
[0010] (3) filtering, washing and drying the product to obtain ZJM-8 molecular sieve;
[0011] (4) calcining the ZJM-8 molecular sieve at 400-800° C. for 2-10 h to obtain the calcined ZJM-8 molecular sieve, i.e., the ZJM-8 molecular sieve product containing phosphorus and aluminum components.
[0012] As a preferred embodiment of the present invention, the aluminum source is at least one of boehmite, aluminum hydroxide, aluminum oxide or aluminum isopropoxide.
[0013] As a preferred embodiment of the present invention, the phosphorus source is phosphoric acid.
[0014] As a preferred embodiment of the present invention, the silicon source is at least one of silica sol, fumed silica, solid silica gel or tetraethyl silicate.
[0015] As a preferred embodiment of the present invention, the template is 1,4-hexaethylbutylammonium hydroxide, and its structural formula is as follows:
[0016]
[0017] The present invention further provides the use of the ZJM-8 molecular sieve containing phosphorus and aluminum components prepared by the aforementioned method as an adsorbent.
[0018] Description of the invention principle:
[0019] The specific structure of molecular sieves is determined by X-ray diffraction patterns (XRD), and different zeolite molecular sieves have different XRD spectra. Currently known molecular sieves all have their own characteristic XRD spectra, so by comparing the XRD spectra of molecular sieve samples with those in the known molecular sieve database, it can be known whether the prepared molecular sieve product has a new molecular sieve topology.
[0020] By comparing the XRD diffraction pattern of the ZJM-8 molecular sieve prepared by the present invention with all known structures, it is known that there is currently no pure aluminum phosphate molecular sieve with the same topological structure as ZJM-8, and the molecular sieve is a pure aluminum phosphate molecular sieve with a completely new topological structure. Based on the brand-new ZJM-8 molecular sieve, the present invention continues to obtain the ZJM-8 molecular sieve by high-temperature roasting. The latter removes the organic structure directing agent (OSDA) filled between the molecular sieve channels relative to the ZJM-8 molecular sieve, but still retains the molecular sieve skeleton structure. After refining the XRD diffraction pattern of the calcined ZJM-8, it is possible to obtain the conclusion that the molecular sieve structure is the same as the ZJM-8 structure.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The calcined ZJM-8 molecular sieve in the present invention is a new type of phosphorus aluminum molecular sieve, which has a novel molecular sieve topological structure and enriches the types of molecular sieves. Therefore, the proposal of the present invention has an important role in exploring the synthesis of new molecular sieve framework structures.
[0023] 2. The molecular sieve of the present invention has a high internal pore utilization rate and a large specific surface area in its skeleton structure, and has a wide application prospect as an adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the XRD diagram of the ZJM-8 molecular sieve material prepared in Example 1 of the present invention.
[0025] Figure 2 This is a SEM image of the ZJM-8 molecular sieve material prepared in Example 1 of the present invention.
[0026] Figure 3 This is the XRD diagram of the calcined ZJM-8 molecular sieve material prepared in Example 1 of the present invention.
[0027] Figure 4 This is a SEM image of the calcined ZJM-8 molecular sieve material prepared in Example 1 of the present invention.
[0028] Figure 5 This is the N2 adsorption curve of the calcined ZJM-8 molecular sieve material in the adsorbent application example in Example 1.
[0029] Figure 6 This is the H2O adsorption curve of the calcined ZJM-8 molecular sieve material in the adsorbent application example in Example 1. DETAILED DESCRIPTION
[0030] The specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings, but it should be noted that the method of the present invention is not limited to the following examples and cannot limit the scope of protection of the present invention.
[0031] Example 1
[0032] 3.60 g (concentration of 0.89 mmol / g) of 1,4-hexaethylbutylammonium hydroxide aqueous solution and 0.69 g of deionized water were placed in a 25 ml beaker, 0.47 g of boehmite (70 wt% Al2O3) was added and stirred evenly, and then 0.74 g (concentration of 85 wt%) of phosphoric acid was added and stirred for 2 hours to form a gel; then the solution was poured into a hydrothermal reactor and crystallized at 200°C for 3 days.
[0033] In the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: template: water is 1:1:1:40.
[0034] After the crystallization, the hydrothermal reactor was cooled to room temperature, the obtained molecular sieve was washed, filtered, dried, and then ground into powder for XRD analysis. The molecular sieve was a new pure aluminum phosphate molecular sieve ZJM-8, such as Figure 1 As shown, the electron microscope photo shows that the molecular sieve is in the shape of hexagonal blocks.
[0035] The sample was calcined at 550℃ for 4 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, such as Figure 3 At the same time, the electron microscope photo shows that the molecular sieve is still in the shape of hexagonal blocks, such as Figure 4 shown.
[0036] In the XRD diffraction data of the ZJM-8 molecular sieve obtained in this example, the 2θ angle of the strongest peak in the range of 5 to 40° is 20.70±0.20; the X-ray diffraction spectrum includes at least the following X-ray diffraction peaks:
[0037]
[0038] Among them, the incident ray of X-ray diffraction is Cu Kα1.
[0039] The X-ray diffraction pattern of the calcined ZJM-8 molecular sieve obtained in this example includes at least the following X-ray diffraction peaks:
[0040]
[0041] Among them, the incident ray of X-ray diffraction is Cu Kα1.
[0042] Example 2
[0043] Place 5.07 g (concentration of 1.26 mmol / g) of 1,4-hexaethylbutylammonium hydroxide aqueous solution and 1.21 g of deionized water in a 25 ml beaker, add 0.93 g of boehmite (70 wt% Al2O3) and stir evenly, then add 1.03 g (concentration of 85 wt%) of phosphoric acid and stir for 2 hours to form a gel, add 0.08 g of solid silica gel, continue stirring for 2 hours, then pour into a hydrothermal reactor and crystallize at 200°C for 3 days.
[0044] Among the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: silicon source calculated as SiO2: template: water is 1:0.7:0.2:1:40.
[0045] After the crystallization, the hydrothermal reactor was cooled to room temperature, the obtained molecular sieve was washed, filtered, dried, and then ground into powder for XRD analysis. The molecular sieve was a new pure aluminum phosphate molecular sieve ZJM-8, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.
[0046] The sample was calcined at 400°C for 10 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, which was similar to the XRD diffraction pattern of the calcined ZJM-8 molecular sieve in Example 1, and the diffraction peak data was similar to that in Example 1. At the same time, the electron microscope photo showed that the morphology of the molecular sieve was still hexagonal block.
[0047] Example 3
[0048] 5.07 g (concentration of 1.26 mmol / g) of 1,4-hexaethylbutylammonium hydroxide aqueous solution and 0.57 g of deionized water were placed in a 25 ml beaker, 1.0 g of aluminum hydroxide was added and stirred evenly, and then 1.03 g (concentration of 85 wt%) of phosphoric acid was added and stirred for 2 hours to form a gel; then the mixture was poured into a hydrothermal reactor and crystallized at 180°C for 7 days.
[0049] In the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: template: water is 1:1.3:1:40.
[0050] After the crystallization, the hydrothermal reactor was cooled to room temperature, the obtained molecular sieve was washed, filtered, dried, and then ground into powder for XRD analysis. The molecular sieve was a new pure aluminum phosphate molecular sieve ZJM-8, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.
[0051] The sample was calcined at 800°C for 2 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, which was similar to the XRD diffraction pattern of the calcined ZJM-8 molecular sieve in Example 1, and the diffraction peak data was similar to that in Example 1. At the same time, the electron microscope photo showed that the morphology of the molecular sieve was still hexagonal block.
[0052] Example 4
[0053] 2.53 g (concentration of 1.26 mmol / g) of 1,4-hexaethylbutyl ammonium hydroxide aqueous solution and 2.36 g of deionized water were placed in a 25 ml beaker, 2.0 g of aluminum isopropoxide was added and stirred evenly, and then 1.92 g (concentration of 85 wt%) of phosphoric acid was added and stirred for 2 hours to form a gel; 0.61 g (40 wt% SiO2) of silica sol was added and stirring was continued for 2 hours, and then poured into a hydrothermal reactor and crystallized at 200°C for 3 days.
[0054] The molar ratio of the aluminum source calculated as Al2O3: the phosphorus source calculated as P2O5: the silicon source calculated as SiO2: the template: water in the raw materials used in the above operation is 1:1:0.5:1:40.
[0055] After the crystallization, the hydrothermal reactor was cooled to room temperature, the obtained molecular sieve was washed, filtered, dried, and then ground into powder for XRD analysis. The molecular sieve was a new pure aluminum phosphate molecular sieve ZJM-8, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.
[0056] The sample was calcined at 550°C for 4 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, which was similar to the XRD diffraction pattern of the calcined ZJM-8 molecular sieve in Example 1, and the diffraction peak data was similar to that in Example 1. At the same time, the electron microscope photo showed that the morphology of the molecular sieve was still hexagonal block.
[0057] Example 5
[0058] 7.60 g (concentration of 0.89 mmol / g) of 1,4-hexaethylbutyl ammonium hydroxide aqueous solution was placed in a 25 ml beaker, 0.93 g of boehmite (70 wt% Al2O3) was added and stirred evenly, then 1.48 g (concentration of 85 wt%) of phosphoric acid was added and stirred for 2 hours to form a gel; 0.12 g of fumed silica was added and stirring was continued for 2 hours, 0.68 g of water was dried off the gel under stirring, and finally poured into a hydrothermal reactor and crystallized at 200°C for 3 days.
[0059] Among the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: silicon source calculated as SiO2: template: water is 1:1:0.3:1.5:20.
[0060] After the crystallization is completed, the hydrothermal reactor is cooled to room temperature, and the obtained molecular sieve is washed, filtered, and dried to obtain a ZJM-8 molecular sieve. Then it is ground into powder for XRD analysis. The molecular sieve is a new pure aluminum phosphate molecular sieve ZJM-8, and its XRD diffraction pattern is similar to that of Example 1, and the diffraction peak data is similar to that of Example 1. The electron microscope photo shows that the molecular sieve is still in a hexagonal block.
[0061] The sample was calcined at 550°C for 4 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, which was similar to the XRD diffraction pattern of the calcined ZJM-8 molecular sieve in Example 1, and the diffraction peak data was similar to that in Example 1. At the same time, the electron microscope photo showed that the morphology of the molecular sieve was still hexagonal block.
[0062] Example 6
[0063] 7.60 g (concentration: 1.26 mmol / g) of 1,4-hexaethylbutylammonium hydroxide aqueous solution and 39.52 g of deionized water were placed in a 50 ml beaker, 0.65 g of Al2O3 was added and stirred evenly, and then 1.92 g (concentration: 85 wt%) of phosphoric acid was added and stirred for 2 hours to form a gel; then the mixture was poured into a hydrothermal reactor and crystallized at 250°C for 1 day.
[0064] In the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: template: water is 1:1:0.5:100.
[0065] After the crystallization, the hydrothermal reactor was cooled to room temperature, the obtained molecular sieve was washed, filtered, dried, and then ground into powder for XRD analysis. The molecular sieve was a new pure aluminum phosphate molecular sieve ZJM-8, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.
[0066] The sample was calcined at 550°C for 4 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, which was similar to the XRD diffraction pattern of the calcined ZJM-8 molecular sieve in Example 1, and the diffraction peak data was similar to that in Example 1. At the same time, the electron microscope photo showed that the morphology of the molecular sieve was still hexagonal block.
[0067] Example 7
[0068] 7.60 g (concentration of 0.89 mmol / g) of 1,4-hexaethylbutyl ammonium hydroxide aqueous solution was placed in a 25 ml beaker, 0.93 g of boehmite (70 wt% Al2O3) was added and stirred evenly, then 1.48 g (concentration of 85 wt%) of phosphoric acid was added and stirred for 2 hours to form a gel; 0.80 g of tetraethyl silicate was added and stirring was continued for 2 hours, 0.68 g of water was dried off the gel under stirring, and finally poured into a hydrothermal reactor and crystallized at 200°C for 3 days.
[0069] Among the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: silicon source calculated as SiO2: template: water is 1:1:0.6:1.5:20.
[0070] After the crystallization is completed, the hydrothermal reactor is cooled to room temperature, and the obtained molecular sieve is washed, filtered, and dried to obtain a ZJM-8 molecular sieve. Then it is ground into powder for XRD analysis. The molecular sieve is a new pure aluminum phosphate molecular sieve ZJM-8, and its XRD diffraction pattern is similar to that of Example 1, and the diffraction peak data is similar to that of Example 1. The electron microscope photo shows that the molecular sieve is still in a hexagonal block.
[0071] The sample was calcined at 550°C for 4 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, which was similar to the XRD diffraction pattern of the calcined ZJM-8 molecular sieve in Example 1, and the diffraction peak data was similar to that in Example 1. At the same time, the electron microscope photo showed that the morphology of the molecular sieve was still hexagonal block.
[0072] Application examples as adsorbent:
[0073] The calcined ZJM-8 molecular sieve in Example 1 was used in the following ways:
[0074] Take 0.1g of calcined ZJM-8 molecular sieve powder, and after pretreatment at 300℃ for 10 hours, measure the N2 adsorption of the calcined ZJM-8 molecular sieve at liquid nitrogen temperature. The adsorption curve is as follows: Figure 5 The adsorption curve was analyzed and the specific surface area of the calcined ZJM-8 molecular sieve was 583 m 2 / g.
[0075] Take 0.12g of calcined ZJM-8 molecular sieve powder, after pretreatment at 200℃ for 10 hours, measure the H2O vapor adsorption of the calcined ZJM-8 molecular sieve at room temperature, and the adsorption curve is as follows: Figure 6 The adsorption curve is analyzed and the water adsorption capacity of the calcined ZJM-8 molecular sieve is about 27wt.%.
[0076] It can be seen from the above results that the calcined ZJM-8 in Example 1 can adsorb N2 and H2O.
[0077] Similar analysis results can be obtained by using the calcined ZJM-8 molecular sieve in Example 2-7 in the same manner as above. Considering that the specific surface area of the ZSM-5 molecular sieve product in the prior art is usually 350m 2 / g, and the water adsorption capacity is usually about 8wt.%. Compared with ZSM-5 molecular sieve, the calcined ZJM-8 molecular sieve prepared by the present invention has better adsorption capacity, so the product can play an important role in the field of gas adsorption separation.
Claims
1. A method for preparing ZJM-8 molecular sieve containing phosphorus and aluminum, characterized in that: include: (1) A template solution is prepared by combining a template and water, and an aluminum source, a phosphorus source and a silicon source are added in sequence under stirring, and the mixture is uniformly mixed to form a gel; wherein the molar ratio of the aluminum source calculated as Al2O3: the phosphorus source calculated as P2O5: the silicon source calculated as SiO2: the template: water is 1: (0.7-1.3): (0-0.6): (0.5-1.5): (20-100); The aluminum source is at least one of boehmite, aluminum hydroxide, aluminum oxide or aluminum isopropoxide; the phosphorus source is phosphoric acid; the silicon source is at least one of silica sol, fumed silica, solid silica gel or tetraethyl silicate; the template is 1,4-hexaethylbutyl ammonium hydroxide; (2) transferring the gel to a hydrothermal reactor for hydrothermal crystallization reaction; the reaction temperature is 180 to 250 °C, and the reaction time is 1 to 7 days; (3) filtering, washing and drying the product to obtain ZJM-8 molecular sieve; (4) calcining the ZJM-8 molecular sieve at 400-800°C for 2-10 h to obtain the calcined ZJM-8 molecular sieve, i.e., the ZJM-8 molecular sieve product containing phosphorus and aluminum components.
2. Use of the ZJM-8 molecular sieve containing phosphorus and aluminum prepared by the method according to claim 1 as an adsorbent.
Citation Information
Patent Citations
1,4-hexaethyl butanediamine hydroxide, preparation method and application
CN107235846A
AFN structure silicon-phosphorus-aluminum molecular sieve, as well as preparation method and application thereof
CN108147423A
Organic template agent, preparation method and application thereof, high-silicon KFI zeolite molecular sieve, and preparation method and application of high-silicon KFI zeolite molecular sieve
CN114105166A
Cited By
Preparation method and application of ZJM-11 molecular sieve containing phosphorus and aluminum components
CN122561972A